Research on Factors Influencing Customers' Online Green Packaging Purchase Decisions at OneAds Digital Company Limited - Nguyen, Thi Thu Ha (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - E-commerce Management; 2021-2025.